Effect of Community Participation, Knowledge Transfer, Technology Adoption on Community Food Security and Agricultural Sustainability: A study on farmer entrepreneurs in Indonesia - Kuswarini Sulandjari; Zainal Abidin; Mitra Musika Lubis; Diah Retno Dwi Hastuti (West Science Interdisciplinary Studies, 2023)
In the context of agricultural entrepreneurship in Indonesia, this quantitative study explores the intricate relationships that exist between community engagement, knowledge transfer, technology adoption, community food security, and agricultural sustainability. To look into the connections between these crucial factors, the study included 350 agricultural entrepreneurs from various parts of Indonesia in a representative sample. Structural equation modeling using partial least squares (SEM-PLS) was used to gather and analyze data. The findings provided insights into the significance of community engagement, knowledge sharing, and technological advancement in guaranteeing food security. They also confirmed the significant positive direct effects of community participation, knowledge transfer, and technology adoption on community food security. Furthermore, the research findings indicate that the relationship between agricultural sustainability and community engagement is mediated by knowledge transfer and technological adoption, underscoring their crucial function in advancing sustainable agricultural practices. These results add to our knowledge of the dynamics of agricultural entrepreneurship in Indonesia and have important ramifications for stakeholders and policymakers who want to enhance the region's agricultural sustainability and food security.